The "Construction" of Chinese culture in a globalized world and its importance for Beijing's smart power: Notes and concepts on a narrative shift - Alessandra Cappelletti (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2017)
The aim of this paper is to unveil the main cultural patterns adopted by the Chinese leadership to project smart power abroad, and to provide a new perspective on the claims by Chinese scholars and politicians who argue that a new paradigm in international relations is being promoted by Beijing. Principles as "inclusiveness", "in-win cooperation", "peaceful rise", "harmonious world" - often raised in relation with China's vision for a new global order and its flagship policy, the Belt and Road Initiative (BRI) - are part of a new narrative which cannot replace, for instance, fundamental issues as a clear regulatory framework needed for enterprises willing to participate in BRI-related infrastructural and energy projects. The lack of a clear legal framework is at the moment one of the most important problem hindering foreign firms' ability to invest and grow within the China-led initiative. The importance of this study rests on the necessity to find new interpretative insights to understand the main driving forces behind China's foreign policy (often not complying with Western-set rules and practices) by assessing the role of Chinese classical culture in the projection of China's smart power. The main cultural patterns and perspectives guiding Chinese policies abroad; the possibility that the Chinese government is introducing a narrative shift in global policy practices; the surfacing of a possible new way for international relations consistently based on an effort to improve international relations and enhance the state of world affairs, or maybe simply of a strategic scheme meant to avoid creating a clearer framework which could guarantee access to the initiative to all interested parts, at the same time limiting Beijing's power to arbitrarily choose partners and directions, will all be objects of reflection.
Keywords: 330; cultural diplomacy; soft power; smart power; Chinese politics; knowledge construction; cultural narratives; identity